1989
DOI: 10.1177/073953298901000207
|View full text |Cite
|
Sign up to set email alerts
|

Black & White. Unread All over?: How Design & Color Affect Reader Judgment of Newspapers

Abstract: A study of design and color effects on newspaper credibility indicates that earlier notions that readers equate modern color and layout with lack of professionalism may be faulty. The present study finds that readers judge color and design charactistics less harshly than previously thought and that characteristics other than design considerations “color” readers' views of newspaper value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The findings support studies done by Smith (1989). which found that readers rated a publication more highly in the evaluative factor if it used color: by Stempel and Click (1976).…”
Section: Discussion Of Brochure Evaluationsupporting
confidence: 88%
See 3 more Smart Citations
“…The findings support studies done by Smith (1989). which found that readers rated a publication more highly in the evaluative factor if it used color: by Stempel and Click (1976).…”
Section: Discussion Of Brochure Evaluationsupporting
confidence: 88%
“…Pasternack and Utt (1986) cautioned newspapers against use of color lest they be viewed as less than trustworthy. However, the above study was replicated later by Smith (1989) with differing results. He hypothesized that students in his study would view the colorful newspapers less harshly than did students in the Pasternak-Utt study.…”
Section: Color In Media Studiesmentioning
confidence: 95%
See 2 more Smart Citations